2017
DOI: 10.1111/bjd.15381
|View full text |Cite
|
Sign up to set email alerts
|

Open-label study of etanercept treatment in patients with moderate-to-severe plaque psoriasis who lost a satisfactory response to adalimumab

Abstract: SummaryBackground Some patients with plaque psoriasis experience secondary failure of tumour necrosis factor inhibitor therapy. Objectives To evaluate efficacy, safety and patient-reported outcomes (PROs) with etanercept in patients with secondary adalimumab failure. Methods This phase IV open-label single-arm estimation study (NCT01543204) enrolled patients on adalimumab who had achieved static Physician's Global Assessment (sPGA) score 0/1 (clear/almost clear). Patients subsequently lost response, defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…A phase IV, open-label, single-arm estimation study evaluated the efficacy of etanercept therapy in patients who previously failed adalimumab. Both patients positive for anti-adalimumab antibodies (ADAs) (47.5% (95% CI: 31.5–63.9)) and patients negative for ADAs (50% (95% CI: 27.2–72.8) achieved PASI-75 after 12 weeks of treatment with etanercept [ 58 ]. The results supported etanercept as a satisfactory treatment for patients with secondary failure to adalimumab, regardless of ADA status [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…A phase IV, open-label, single-arm estimation study evaluated the efficacy of etanercept therapy in patients who previously failed adalimumab. Both patients positive for anti-adalimumab antibodies (ADAs) (47.5% (95% CI: 31.5–63.9)) and patients negative for ADAs (50% (95% CI: 27.2–72.8) achieved PASI-75 after 12 weeks of treatment with etanercept [ 58 ]. The results supported etanercept as a satisfactory treatment for patients with secondary failure to adalimumab, regardless of ADA status [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the high price of biologics, the pharmacoeconomic models and payments should be adjusted to take diminished value into consideration. After all, in the current study, six out of 10 patients were very dissatisfied with a treatment that used to work …”
mentioning
confidence: 67%
“…It is rare that we welcome an imperfect study on a not very hot topic that is paid for by the pharmaceutical industry. In this issue of the BJD , Bagel et al . present the findings of their open‐label study of etanercept treatment in patients no longer responding satisfactorily to adalimumab.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Topicals are the most commonly used medication for managing plaque psoriasis; up to 97.5% of psoriasis patients are reported to use topicals. 22 Despite this and the fact that numerous studies have reported the significant positive impact of biologics on work productivity, 15,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] to the best of our knowledge, there are no studies that have investigated the impact of topicals on work productivity. Fixed-dose combination calcipotriol 50 µg/g/betamethasone dipropionate 0.5 mg/g (Cal/ BD) aerosol foam (Enstilarâ; LEO Pharma A/S, Ballerup, Denmark) is a topical approved for 4 weeks of treatment for psoriasis vulgaris in the United States 37 (for adults and adolescents) and the EU 38 (for adults only).…”
Section: Introductionmentioning
confidence: 99%